« Gênes 2001 », événement de longue durée - Maxime Boidy; Marie Fabre; Alice Leroy (Laboratoire Italien)
The twelve contributions in this Laboratoire italien issue examine the record of the Genoa G8 counter-summit in July 2001, twenty years after its ferocious repression by the Italian police, by cross-referencing perspectives from social sciences, literary studies, oral narratives, film studies and visual studies.